Contructing Climate Change Scenarios for Ho Chi Minh City - Van Khiem, Mai (VNU Journal of Science: Earth and Environmental Sciences, 2018)
Abstract: This article presents the results of constructing climate change scenarios for Ho Chi Minh City (HCMC) based on the climate change scenarios of Vietnam published in 2016 by the Ministry of Natural Resources and Environment. Four high-resolution regional climate models including CCAM, clWRF, PRECIS, and RegCM were used to downscale the results of global climate models. The results show that the annual average temperature in HCMC tends to increase in the future compared to the baseline period 1986 - 2005, the increase depends on each RCP scenario. By the end of the century, the annual average temperature in HCMC has an increase of about 1.7÷1.9°C under the RCP4.5 scenario and 3.2÷3.6°C under RCP8.5. Meanwhile, annual rainfall in HCMC tends to increase in most periods under both of RCP scenarios. By the end of the century, annual rainfall in HCMC increases from 15% to 25% in the RCP4.5 and 20-25% in the RCP8.5 scenarios, respectively. Annual rainfall in coastal areas increaseslarger than in inland areas. Keywords: Climate change scenarios, Ho Chi Minh City. References: [1] IPCC (1990), Contribution of Working Group 1 to the First Assessment Report of the Intergovernmental Panel on Climate Change, Cambridge University Press, Cambridge, United Kingdom; New York, NY, USA, p. 365. [2] IPCC (1995), Contribution of Working Group I to the Second Assessment Report of the Intergovernmental Panel on Climate Change, Cambridge University Press, Cambridge, United Kingdom; New York, NY, USA, p. 588. [3] IPCC (2001), Contribution of Working Group I to the Third Assessment Report of the Intergovernmental Panel on Climate Change, Cambridge University Press, Cambridge, United Kingdom; New York, NY, USA, p. 881. [4] IPCC (2007), Contribution of Working Group I to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change, Cambridge University Press, Cambridge, United Kingdom; New York, NY, USA, p. 996. [5] Bộ Tài nguyên Môi trường (2003), Thông báo lân thứ nhất của Việt Nam cho Công ước khung của Liên Hợp Quốc về Biến đổi khí hậu. [6] Bộ Tài nguyên Môi trường (2009), Kịch bản Biến đổi khí hậu, nước biển dâng cho Việt Nam. [7] Bộ Tài nguyên Môi trường (2012), Kịch bản Biến đổi khí hậu, nước biển dâng cho Việt Nam. [8] Bộ Tài nguyên Môi trường (2016), Kịch bản Biến đổi khí hậu, nước biển dâng cho Việt Nam. [9] IPCC (2013), Climate Change 2013: The Physical Science Basis. Contribution of Working Group I to the Fifth Assessment Report of the Intergovernmental Panel on Climate Change. [10] Mishra, K., B. and Herath, S. (2014). Assessment of Future Floods in the Bagmati River Basin of Nepal Using Bias-Corrected Daily GCM Precipitation Data, J. Hydrol. Eng., 10.1061 /(ASCE) HE.1943-5584.0001090, 05014027. [11] Amengual A, Homar V, Romero R, Alonso S, Ramis C (2012),A statistical adjustment of regional climate model outputs to local scales: application to Platja de Palma, Spain. J Clim 25:939-957.